A high performance epoxy adhesive and its application in screen printing

By using high-performance epoxy adhesive in screen printing, the solvent resistance of screen film in silver paste and the problems of lag and grating breaking during the printing process are solved, and efficient printing and long life are achieved.

CN116445116BActive Publication Date: 2025-03-14江苏亚龙电子科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310430837.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2025-03-14
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

In the production of photovoltaic cell cells, in screen printing technology, the screen film needs to be immersed in silver paste containing organic solvents for a long time, and it needs to undergo multiple scraping and extrusion printing, resulting in the screen film having excellent solvent resistance, flexibility and wear resistance, and avoiding problems such as hysteresis and grid breakage during the printing process.

Method used

It provides a high-performance epoxy adhesive that has excellent solvent resistance, flexibility, wear resistance and good mechanical properties after thermal curing, and is especially suitable for screen printing. The epoxy glue formula includes epoxy resin, vapor phase silica, curing agent, silicone resin, toughening agent, accelerator and additives, and is prepared by a specific stirring and drying process.

Benefits of technology

This high-performance epoxy adhesive exhibits efficient printing performance and long service life in screen printing, has excellent solvent resistance and high peel strength, which can effectively prevent hysteresis and gate breakage, and improve printing quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004190234230000021
    Figure BDA0004190234230000021
  • Figure BDA0004190234230000031
    Figure BDA0004190234230000031
  • Figure BDA0004190234230000051
    Figure BDA0004190234230000051
Patent Text Reader

Abstract

The present invention belongs to the field of screen printing, and in particular to a high-performance epoxy adhesive and its application in screen printing. The components include epoxy resin, fumed silica, silicone resin, curing agent, accelerator, toughening agent, and auxiliary agent. After curing, the epoxy resin adhesive has a stable structure, high peel strength, and excellent solvent resistance. The fumed silica is filled into the gaps in the polymer chain and bonds with the epoxy group, thereby increasing the strength and toughness of the epoxy resin. When used as screen glue for screen printing, the silica is exposed on the adhesive surface, which is conducive to the flow and rapid penetration of silver paste, prevents broken grids, and improves printability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of screen printing, and in particular relates to a high-performance epoxy adhesive and an application thereof in screen printing. Background Art

[0002] In the process of manufacturing photovoltaic cells, highly active metal paste is printed onto silicon wafers through screen printing technology to form the required electrodes and electric field patterns. The metal paste is solidified by drying and then rapidly sintered at high temperature. With the help of active substances, an alloy layer is formed between the metal and the surface of the silicon wafer.

[0003] During printing, the screen film on the silk screen needs to be immersed in silver paste containing organic solvents for a long time, and needs to undergo hundreds of thousands of times of scraping and extrusion printing. Therefore, not only is the screen film required to have excellent solvent resistance, flexibility and wear resistance, but the printability of the silver paste must also be fully considered to avoid problems such as lag and broken grids during the printing process. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-performance epoxy adhesive, which has excellent solvent resistance, flexibility, wear resistance and good mechanical properties after thermal curing, and is especially applied to screen printing, showing high-efficiency printing performance and service life.

[0005] The epoxy adhesive is calculated by weight and includes 100 parts of epoxy resin, 0.5-1.5 parts of fumed silica, 1-3 parts of curing agent, 2-5 parts of silicone resin, 3-6 parts of toughening agent, and 0.2-0.5 parts of accelerator. The surface of fumed silica contains hydroxyl groups.

[0006] It can also include 0.2 to 0.5 parts of auxiliary agents.

[0007] The epoxy resin is selected from one or a combination of glycidyl epoxy, alicyclic epoxy, bisphenol A epoxy and phenolic modified epoxy.

[0008] Fumed silica is selected from a material having a specific surface area of ​​120 m 2 / g, 170m 2 / g and 260m 2 / g one or a combination of several,

[0009] The silicone resin is selected from one or a combination of polymethyl silicone resin, polyethyl silicone resin and polyaryl silicone resin.

[0010] The curing agent is one or a combination of ethyleneamine, dicyandiamide or ketimine.

[0011] The accelerator is 2-methylimidazole or substituted urea.

[0012] The toughening agent is selected from one or a combination of PU modified epoxy, polyether modified epoxy or dimer acid modified epoxy.

[0013] The additives include defoamers and leveling agents. The defoamers are BYK-006N, BYK-A530 or BYK-A550 from BYK, and the leveling agents are BYK-333, BYK-330 or BYK-346 from BYK.

[0014] The preparation of the above-mentioned epoxy adhesive comprises the following steps:

[0015] (1) The epoxy resin, fumed silica, silicone resin, toughening agent, diluent and additive are mixed thoroughly at a stirring speed of 800 to 1000 rpm for 15 to 30 minutes.

[0016] (2) adding a curing agent to the mixture obtained in step (1) and mixing thoroughly,

[0017] The stirring speed during mixing is 800 to 1000 rpm and the stirring time is 5 to 10 minutes.

[0018] (3) adding the accelerator to the mixture obtained in step (2) and mixing thoroughly,

[0019] The stirring speed during mixing is 800 to 1000 rpm and the stirring time is 5 to 10 minutes.

[0020] (4) coating the mixture obtained in step (3) on the base film, drying to obtain a film-like epoxy adhesive, and pasting a release film on one side of the film-like epoxy adhesive, and rolling it up.

[0021] The base film is a polyimide film, the speed during coating is 2-3 m / min, and the drying temperature is 60-80°C.

[0022] The present invention also provides an application of the epoxy adhesive in screen printing: the epoxy adhesive is attached to the screen surface of the screen and hot-pressed to form a screen for screen printing.

[0023] The hot pressing temperature was 190°C, the hot pressing pressure was 3 MPa, and the hot pressing time was 20 min.

[0024] In the present invention, the epoxy resin glue is thermosetting after curing, and has a very stable structure, high peel strength, and excellent solvent resistance. After adding fumed silica to the epoxy resin and fully and evenly dispersing it, the nano-scale silica particles can fill the gaps in the polymer chain. At the same time, the fumed silica is not surface treated in this solution, so the surface of the fumed silica has hydroxyl groups, which can form a bond with the epoxy group, further increasing the strength and toughness of the epoxy resin. When used as a screen adhesive film in screen printing applications, the exposed adhesive surface of the scraper surface and the side wall of the wire groove contains silica, which is conducive to the flow and rapid penetration of silver paste, prevents grid breakage, etc., and improves printability. DETAILED DESCRIPTION

[0025] Example 1

[0026] According to the weight parts of each component in the following table,

[0027]

[0028]

[0029] (1) Add diglycidyl adipate, alicyclic epoxy UVR-6128, fumed silica, dimethyl silicone oil, phenyl methyl silicone oil, Dow DER 791, N,N-dimethylformamide, BYK-006N, and BYK-330 into a reaction kettle, and stir at a speed of 900 rpm for 25 minutes.

[0030] (2) adding dicyandiamide to the mixture obtained in step (1), and mixing and stirring at a speed of 900 rpm for 6 minutes,

[0031] (3) adding 2-methylimidazole to the mixture obtained in step (2), and mixing and stirring at a speed of 900 rpm for 5 minutes.

[0032] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 2 m / min, baking in an oven at 68° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0033] Example 2

[0034] According to the weight parts of each component in the following table,

[0035] Raw material name Number of copies Bisphenol A epoxy E51 60 Epoxy F51 40 <![CDATA[Fumed silica (170 m 2 / g)]]> 1 Dimethicone 2 Diethyl silicone oil 3 Dicyandiamide 3 2-Methylimidazole 0.3 664 polyether epoxy resin 4 Toluene 150 BYK-A530 0.1 BYK-333 0.2

[0036] (1) Add bisphenol A epoxy E51, epoxy F51, fumed silica, dimethyl silicone oil, diethyl silicone oil, 664 polyether epoxy resin, toluene, BYK-A530, and BYK-333 into a reaction kettle and mix and stir at a speed of 800 rpm for 30 minutes.

[0037] (2) adding dicyandiamide to the mixture obtained in step (1), and mixing and stirring at a speed of 800 rpm for 8 minutes,

[0038] (3) adding 2-methylimidazole to the mixture obtained in step (2), and mixing and stirring at a speed of 800 rpm for 5 minutes.

[0039] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 2.5 m / min, baking in an oven at 72° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0040] Example 3

[0041] According to the weight parts of each component in the following table,

[0042] Raw material name Number of copies Alicyclic Epoxy UVR-6128 80 Bisphenol A epoxy E44 20 <![CDATA[Fumed silica (260 m 2 / g)]]> 0.5 Diethyl silicone oil 1 Phenyl methyl silicone oil 2 Diethylenetriamine 3 Dyhard UR500 0.3 664 polyether epoxy resin 2 Dimer acid modified epoxy EPD-172L 3 Xylene 200 BYK-A550 0.2 BYK-346 0.1

[0043] (1) Add alicyclic epoxy UVR-6128, bisphenol A epoxy E44, fumed silica, diethyl silicone oil, phenyl methyl silicone oil, 664 polyether epoxy resin, dimer acid modified epoxy EPD-172L, xylene, BYK-A550, and BYK-346 into a reaction kettle and mix and stir at a speed of 850 rpm for 20 minutes.

[0044] (2) adding diethylenetriamine to the mixture obtained in step (1), and mixing and stirring at a speed of 850 rpm for 10 minutes.

[0045] (3) Add Dyhard UR500 to the mixture obtained in step (2), and mix and stir at a speed of 850 rpm for 10 minutes.

[0046] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 3 m / min, baking in an oven at 60° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0047] Example 4

[0048] According to the weight parts of each component in the following table,

[0049] Raw material name Number of copies Neopentyl glycol diglycidyl ether 60 Bisphenol A epoxy E51 40 <![CDATA[Fumed silica (260 m 2 / g)]]> 0.5 Dimethicone 5 Diethylenetriamine 2 Dyhard UR500 0.5 Dow DER 791 3 Dimer acid modified epoxy EPD-172L 3 N,N-Dimethylformamide 150 BYK-A550 0.2 BYK-333 0.3

[0050] (1) Neopentyl glycol diglycidyl ether, bisphenol A epoxy E51, fumed silica, dimethyl silicone oil, Dow DER 791, dimer acid modified epoxy EPD-172L, N,N-dimethylformamide, BYK-A550, and BYK-333 were added to a reaction kettle and mixed and stirred at a speed of 1000 rpm for 18 minutes.

[0051] (2) adding diethylenetriamine to the mixture obtained in step (1), and mixing and stirring at a speed of 1000 rpm for 5 minutes.

[0052] (3) Add Dyhard UR500 to the mixture obtained in step (2), and mix and stir at a speed of 1000 rpm for 5 minutes.

[0053] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 2 m / min, baking in an oven at 80° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0054] Example 5

[0055] According to the weight parts of each component in the following table,

[0056]

[0057]

[0058] (1) Add alicyclic epoxy UVR-6128, bisphenol A epoxy E44, fumed silica, diethyl silicone oil, phenyl methyl silicone oil, 664 polyether epoxy resin, dimer acid modified epoxy EPD-172L, xylene, BYK-A550, and BYK-346 into a reaction kettle and mix and stir at a speed of 850 rpm for 20 minutes.

[0059] (2) adding diethylenetriamine to the mixture obtained in step (1), and mixing and stirring at a speed of 850 rpm for 10 minutes.

[0060] (3) Add Dyhard UR500 to the mixture obtained in step (2), and mix and stir at a speed of 850 rpm for 10 minutes.

[0061] (4) The mixture obtained in step (3) is coated on a polyimide film at a speed of 3 m / min. After coating, the mixture is placed in an oven at 60° C. and dried to obtain a film-like epoxy adhesive. A release film is attached to one side of the film-like epoxy adhesive and the film is rolled up. Comparative Example 1 does not add fumed silica, and the rest is the same as Example 1.

[0062] According to the weight parts of each component in the following table,

[0063]

[0064]

[0065] (1) Add diglycidyl adipate, alicyclic epoxy UVR-6128, dimethyl silicone oil, phenyl methyl silicone oil, Dow DER 791, N,N-dimethylformamide, BYK-006N, and BYK-330 into a reaction kettle, and stir at a speed of 900 rpm for 25 minutes.

[0066] (2) adding dicyandiamide to the mixture obtained in step (1), and mixing and stirring at a speed of 900 rpm for 6 minutes,

[0067] (3) adding 2-methylimidazole to the mixture obtained in step (2), and mixing and stirring at a speed of 900 rpm for 5 minutes.

[0068] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 2 m / min, baking in an oven at 68° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0069] Comparative Example 2: The fumed silica was subjected to hydrophobic surface treatment in advance, and the rest was the same as in Example 2.

[0070] According to the weight parts of each component in the following table,

[0071] Raw material name Number of copies Bisphenol A epoxy E51 60 Epoxy F51 40 <![CDATA[Fumed silica (170 m 2 / g)]]> 1 Dimethicone 2 Diethyl silicone oil 3 Dicyandiamide 3 2-Methylimidazole 0.3 664 polyether epoxy resin 4 Toluene 150 BYK-A530 0.1 BYK-333 0.2

[0072] (1) Add bisphenol A epoxy E51, epoxy F51, fumed silica, dimethyl silicone oil, diethyl silicone oil, 664 polyether epoxy resin, toluene, BYK-A530, and BYK-333 into a reaction kettle and mix and stir at a speed of 800 rpm for 30 minutes.

[0073] (2) adding dicyandiamide to the mixture obtained in step (1), and mixing and stirring at a speed of 800 rpm for 8 minutes,

[0074] (3) adding 2-methylimidazole to the mixture obtained in step (2), and mixing and stirring at a speed of 800 rpm for 5 minutes.

[0075] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 2.5 m / min, baking in an oven at 72° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0076] Comparative Example 3 did not add fumed silica, and the rest was the same as Example 3

[0077] According to the weight parts of each component in the following table,

[0078] Raw material name Number of copies Alicyclic Epoxy UVR-6128 80 Bisphenol A epoxy E44 20 Diethyl silicone oil 1 Phenyl methyl silicone oil 2 Diethylenetriamine 3 Dyhard UR500 0.3 664 polyether epoxy resin 2 Dimer acid modified epoxy EPD-172L 3 Xylene 200 BYK-A550 0.2 BYK-346 0.1

[0079] (1) Add alicyclic epoxy UVR-6128, bisphenol A epoxy E44, diethyl silicone oil, phenyl methyl silicone oil, 664 polyether epoxy resin, dimer acid modified epoxy EPD-172L, xylene, BYK-A550, and BYK-346 into a reaction kettle and mix and stir at a speed of 850 rpm for 20 minutes.

[0080] (2) adding diethylenetriamine to the mixture obtained in step (1), and mixing and stirring at a speed of 850 rpm for 10 minutes.

[0081] (3) Add Dyhard UR500 to the mixture obtained in step (2), and mix and stir at a speed of 850 rpm for 10 minutes.

[0082] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 3 m / min, baking in an oven at 60° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0083] Comparative Example 4: The fumed silica was subjected to hydrophobic surface treatment in advance, and the rest was the same as in Example 4.

[0084] According to the weight parts of each component in the following table,

[0085] Raw material name Number of copies Neopentyl glycol diglycidyl ether 60 Bisphenol A epoxy E51 40 <![CDATA[Fumed silica (260 m 2 / g)]]> 0.5 Dimethicone 5 Diethylenetriamine 2 Dyhard UR500 0.5 Dow DER 791 3 Dimer acid modified epoxy EPD-172L 3 N,N-Dimethylformamide 150 BYK-A550 0.2 BYK-333 0.3

[0086] (1) Neopentyl glycol diglycidyl ether, bisphenol A epoxy E51, fumed silica, dimethyl silicone oil, Dow DER 791, dimer acid modified epoxy EPD-172L, N,N-dimethylformamide, BYK-A550, and BYK-333 were added to a reaction kettle and mixed and stirred at a speed of 1000 rpm for 18 minutes.

[0087] (2) adding diethylenetriamine to the mixture obtained in step (1), and mixing and stirring at a speed of 1000 rpm for 5 minutes.

[0088] (3) Add Dyhard UR500 to the mixture obtained in step (2), and mix and stir at a speed of 1000 rpm for 5 minutes.

[0089] (4) coating the mixture obtained in step (3) on a polyimide film at a speed of 2 m / min, baking in an oven at 80° C. to obtain a film-like epoxy adhesive after sufficient drying, affixing a release film to one side of the film-like epoxy adhesive, and rolling it up.

[0090] The products in the above-mentioned embodiments and comparative examples were unwound and the release films were peeled off. One side of the epoxy adhesive was attached to the screen surface, and a high-precision screen printing screen was made by hot pressing at 190°C and 3MPa for 20 minutes. A line groove was formed on the screen by laser processing. The line groove had a width of 21 microns and a depth of 10 microns.

[0091] A silver paste printing test was carried out on the above-obtained screen. The components of the silver paste used in the test were 70 parts by weight of silver powder, 5 parts by weight of bisphenol A epoxy resin E51, 1 part by weight of dicyandiamide, 1 part by weight of dispersant BP5040, 0.6 parts by weight of KH550, and 10 parts by weight of dimethyl adipate. During the printing process, the scraper slid along the length direction of each groove, the printing pressure was 65N, the printing speed was 410mm / s, and the amount of silver paste was kept sufficient.

[0092] The number of screens tested in each embodiment and comparative example is 10, and the test results are averaged. The experimental results are shown in the following table:

[0093]

[0094] Compared with Example 1 and Example 3, it can be seen that the addition of fumed silica enhances the epoxy resin system and improves the printability. The improvement in printability is particularly evident on the printing screen with a microscopic wire groove structure. On the one hand, the surface of the untreated fumed silica has hydroxyl groups, which form a bond with the epoxy group to enhance the material strength. At the same time, the fumed silica that exposes the side wall of the wire groove reduces the surface energy of the side wall when it contacts the silver paste, thereby improving the permeability of the silver paste into the wire groove.

[0095] At the same time, since the size of the cable trough itself is very small, if the silica particles are too large, it will cause abnormalities on the film surface and affect the performance of the film.

[0096] Compared with Example 3, Example 5 increases the amount of fumed silica, which may be due to the increase in agglomeration between fumed silica, resulting in a slight decrease in the improvement effect.

[0097] Comparative Examples 2 and 4 were subjected to hydrophobic treatment before adding the fumed silica. It stands to reason that the hydrophobic treatment would be more conducive to dispersion when added to the epoxy organic system. However, from the perspective of the enhancement effect, it was reduced instead. This also reflects that the unmodified fumed silica with hydroxyl groups in this solution forms a stronger bonding effect with the organic resin system after entering the epoxy resin.

Claims

1. An application of epoxy adhesive, characterized in that: The epoxy adhesive is used as a screen for screen printing, and its composition is calculated by weight, including 100 parts of epoxy resin, 0.5-1.5 parts of fumed silica, 2-5 parts of silicone resin, 1-3 parts of curing agent, 0.2-0.5 parts of accelerator, and 3-6 parts of toughening agent. The fumed silica has a specific surface area of ​​120m 2 / g, 170m 2 / g and 260m 2 / g or a combination of the foregoing, wherein the fumed silica is not surface treated.

2. The use of the epoxy adhesive as claimed in claim 1, characterized in that: The epoxy resin is one or a combination of glycidyl epoxy, alicyclic epoxy, bisphenol A epoxy and phenolic modified epoxy.

3. The use of the epoxy adhesive as claimed in claim 1, characterized in that: The organic silicon resin is one or a combination of polymethyl silicone resin, polyethyl silicone resin and polyaryl silicone resin.

4. The use of the epoxy adhesive as claimed in claim 1, characterized in that: The curing agent is one or a combination of vinylamine, dicyandiamide and ketimine.

5. The use of the epoxy adhesive as claimed in claim 1, characterized in that: The accelerator is 2-methylimidazole or substituted urea.

6. The use of the epoxy adhesive as claimed in claim 1, characterized in that: The toughening agent is one or a combination of PU modified epoxy, polyether modified epoxy or dimer acid modified epoxy.

7. The use of the epoxy adhesive as claimed in claim 1, characterized in that: Calculated by weight, the epoxy adhesive also includes 0.2 to 0.5 parts of additives, and the additives include defoaming agents and leveling agents.

Citation Information

Patent Citations

  • Die bond conductive adhesive, preparation method thereof and die bond processing method

    CN115851193A

  • Epoxy adhesive tape for silk-screen printing and preparation method thereof

    CN115895497A